The ASA Physical Status Classification: What Is the Evidence for Recommending Its Use in Veterinary Anesthesia?—A Systematic Review - Portier, Karine; Ida, Keila Kazue (Frontiers in Veterinary Science, 2018)
Background The effectiveness of the American Society of Anesthesiologists (ASA) Physical Status (PS) classification to identify the animals at a greater risk of anesthesia-related death and complications is controversial. In this systematic review, we aimed to analyze studies associating the ASA PS scores with the outcome of anesthesia and to verify whether there was any evidence for recommending the use of the ASA PS in veterinary patients. Methods Research articles found through a systematic literature search were assessed for eligibility, and data were extracted and analyzed using random-effects analysis. Results A total of 15 observational prospective and retrospective studies including 258,298 dogs, cats, rabbits, and pigs were included. The analysis found consistency between the studies showing that dogs, cats and rabbits with an ASA-PS ≥III had 3.26 times (95% CI = 3.04 to 3.49), 4.83 times (95% CI = 3.10 to 7.53), and 11.35 times (95% CI = 2.70 to 47.39), respectively, the risk of anesthesia-related death within 24 hours (dogs) and 72 hours (cats and rabbits) after anesthesia compared with those with an ASA PS <III. In addition, the analysis showed that dogs and cats with ASA PS ≥III had 2.34 times the risk of developing severe hypothermia during anesthesia (95% CI=1.82 to 3.01). Conclusions The simple and practical ASA PS was shown to be a valuable prognostic tool and can be recommended to identify an increased risk of anesthetic mortality until 24-72 hours after anesthesia, and a greater risk of development severe intraoperative hypothermia.